Evaluating Social Policy Scenarios for Tourism Development of Barú Island (Colombia) Using Structural Qualitative Modeling - Ramos-Jiliberto, Rodrigo; Jiliberto Herrera, Rodrigo (Frontiers in Ecology and Evolution, 2021)
Social policies are commonly defined from scattered knowledge. It is hard to find examples of social policy design based on a systemic perspective, and even harder with formal modeling support. To advance in filling this gap, we studied the case of the tourism development on Barú Island. We build a qualitative model of the social-ecological structure of tourism development that is taking place in the locality. Model building was based on experiences and opinions of local stakeholders, gathered through participatory procedures. Using our model, we projected the future states of the system, assuming several hypothetical public policy scenarios. More specifically, we evaluated the system responses to: a) a multivariate business–as–usual (BAU) scenario, and b) two multivariate aprioristic scenarios, pointed to improve expected outcomes. These scenarios were based on the opinions of both stakeholders and experts. We also tested: c) simple (univariate) aposterioristic scenarios, built from the structural analysis of the system using the sensitivity matrix. Finally, we included: d) a trivial (and unattainable) scenario, in which every model variable was increased or decreased at convenience. The outcomes of our scenario analysis were evaluated using four different weight sets applied to the projected states of system variables, representing different strategic priorities: social-economic, environmental, mixed, and plain. Our results show that the projected outcomes differ among the tested scenarios, and the strategic priority to be adopted. However, in all cases the BAU scenario was markedly the worst. For every strategic priority, some simple aposterioristic scenarios performed slightly better, as compared to the more complex aprioristic ones, and even better that the trivial scenario. This result was more noticeable under the plain strategy. We conclude that aposterioristic scenarios derived from the sensitivity matrix of the model, particularly decreasing migration risk and increasing governance strength, are the best candidates for policy-making, among the evaluated alternatives. Our findings suggest that social policy-making can benefit from structural qualitative modeling. This approach may give analytical support to the selection of intervention measures from a structural perspective, based on defined strategic priorities. For this purpose, however, the model and the outcomes obtained from analysis should be updated steadily.